Genistein, a Phytoestrogen in Soybean, Induces the Expression of Acetylcholinesterase via G Protein-Coupled Receptor 30 in PC12 Cells - Liu, Etta Y. L.; Xu, Miranda L.; Jin, Yan; Wu, Qiyun; Dong, Tina T. X.; Tsim, Karl W. K. (Frontiers in Molecular Neuroscience, 2018)
Genistein, 4',5,7-trihydroxyisoflavone, is a major isoflavone in soybean, which is known as phytoestrogen having known benefit to brain functions. Being a common phytoestrogen, the possible role of genistein in the brain protection needs to be further explored. In cultured PC12 cells, application of genistein significantly induced the expression of neurofilaments, markers for neuronal differentiation. In parallel, the expression of tetrameric form of proline-rich membrane anchor (PRiMA)-linked acetyl-cholinesterase (G4 AChE), a key enzyme to hydrolyze acetylcholine in cholinergic synapses, was induced in a dose-dependent manner: this induction included the associated protein PRiMA. The genistein-induced AChE expression was fully blocked by the pre-treatment of H89 (an inhibitor of protein kinase A) and G15 (a selective GPR 30 antagonist), which suggested a direct involvement of a membrane-bound estrogen receptor, named as G protein-coupled receptor 30 (GPR 30) in the cultures. In parallel, the estrogen-induced activation of GPR30 induced AChE expression in a dose-dependent manner. The genistein/estrogen-induced AChE expression was triggered by a cyclic AMP responding element (CRE) located on the ACHE gene promoter. The binding of this CRE site by cAMP response element-binding protein (CREB) induced ACHE gene transcription. In parallel, increased expression levels of miR132 and miR212 were found when cultured PC12 cells were treated with genistein or G1. Thus, a balance between production and destruction of AChE by the activation of GPR 30 was reported here. We have shown for the first time that the activation of GPR30 could be one way for estrogen or flavonoids, possessing estrogenic properties, to enhance cholinergic functions in the brain, which could be a good candidate for possible treatment of neurodegenerative diseases.